Clinical and molecular identification of Newcastle disease virus in naturally infected chicks in Thi-Qar province of Iraq - Hakeem Jawad Kadhim; Abbas Kamil Shlaga; Safaa Hussein Ali (Open Veterinary Journal)
Background: In poultry, despite intense vaccination programs for prevention of Newcastle disease (ND), the ND infection still affects, causing high mortality in most vaccinated flocks.